1998
DOI: 10.1002/lt.500040203
|View full text |Cite
|
Sign up to set email alerts
|

Brain lactate by magnetic resonance spectroscopy during fulminant hepatic failure in the dog

Abstract: A noninvasive test is needed to assess the severity of encephalopathy during fulminant hepatic failure. This feasibility study was designed to compare a noninvasive test, brain lactate measurement by magnetic resonance spectroscopy, with intracranial pressure monitoring in a large animal model of fulminant hepatic failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 46 publications
1
26
1
Order By: Relevance
“…For example, it was previously shown that exposure of primary cultures of rat astrocytes (the cell type shown to selectively exhibit swelling in the brain in ALF) to pathophysiologically relevant concentrations of lactate leads to significant swelling.20 A recent report advocated the use of a noninvasive technique to measure brain lactate in vivo as an evaluation of advanced encephalopathy in ALF. 21 Results of the present study now show that the selective attenuation of ALF-related increases of lactate and alanine in frontal cortex, concomitant with the prevention of encephalopathy and brain edema, resides in the ability of hypothermia to prevent the de novo synthesis of lactate from glucose.…”
Section: Discussionsupporting
confidence: 55%
“…For example, it was previously shown that exposure of primary cultures of rat astrocytes (the cell type shown to selectively exhibit swelling in the brain in ALF) to pathophysiologically relevant concentrations of lactate leads to significant swelling.20 A recent report advocated the use of a noninvasive technique to measure brain lactate in vivo as an evaluation of advanced encephalopathy in ALF. 21 Results of the present study now show that the selective attenuation of ALF-related increases of lactate and alanine in frontal cortex, concomitant with the prevention of encephalopathy and brain edema, resides in the ability of hypothermia to prevent the de novo synthesis of lactate from glucose.…”
Section: Discussionsupporting
confidence: 55%
“…Other mechanisms which have been proposed include impaired glucose (pyruvate) oxidation leading to brain lactate accumulation [6] and [35] and cerebral hyperemia [7], [15] and [16]. For example, a significant correlation exists between brain lactate concentrations and both encephalopathy grade [24] and [35] and EEG changes [10] in ALF. 13C-NMR studies show that mild hypothermia (35 °C), which prevents the encephalopathy and brain edema in experimental ALF, selectively normalizes brain lactate synthesis, but has no effect on glutamine synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This review discusses two of the more widely used hepatotoxins, galactosamine [29][30][31][32][33][34][35][36] and acetaminophen. [37][38][39][40][41][42][43][44] Over the past 30 years, acetaminophen overdose has become the most common cause of FHF in the United Kingdom.…”
Section: Chemical Modelsmentioning
confidence: 99%